2021
DOI: 10.1177/20101058211015801
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions of radiology healthcare workers during the COVID-19 pandemic

Abstract: Background: Medical imaging is vital in the diagnostic workup and evaluation of patients suspected or confirmed to have COVID-19; hence, radiology healthcare workers (HCWs) were an essential part of the early containment response to the pandemic. Radiology services are facing rising demands to introduce stricter infection control measures, and staff are expected to adhere to the new protocols while coping with a surge in patients. Objectives: This study aims to identify the knowledge, attitudes and perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, Ooi et al caution that while extending radiography shifts to 12 h can be effective in the short-term, in the long-term this work pattern is likely to result in burnout. 17 Establishing remote working and training is vitally important at this time to enable radiographers who are isolating or shielding to continue to work from their home. However, only sixty-seven percent of radiographers surveyed felt that their department could facilitate remote working.…”
Section: Table 11mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ooi et al caution that while extending radiography shifts to 12 h can be effective in the short-term, in the long-term this work pattern is likely to result in burnout. 17 Establishing remote working and training is vitally important at this time to enable radiographers who are isolating or shielding to continue to work from their home. However, only sixty-seven percent of radiographers surveyed felt that their department could facilitate remote working.…”
Section: Table 11mentioning
confidence: 99%
“…Elshami et al 16 reiterated this in their study of radiology workers (MayeJune 2020) in the Middle East, North Africa and India, their results indicating a workload increase specifically in general x-ray and Computed Tomography as these were the main modalities used for the diagnosis of COVID-19 and follow-up investigations. Further work by Ooi et al 17 suggested the need for better organisational structure, resources and education to help the workforce deal with these difficulties whilst Shanahan et al 18 highlighted the need for further strategies to support and enhance staff well-being during subsequent waves of the pandemic. The experience of the Diagnostic Radiography (DR) and TR workforce should be evaluated in order that effective service delivery can be maintained, not only for the ongoing and future waves of the COVID-19 pandemic, but also for future challenges presented by delayed treatments, late presenting disease, and staff shortages/burn-out.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies in Singapore and Saudi Arabia align with this observation. 18 , 19 This is due to health professions being female-dominated, because of their caring attribute. 20 Most of the participants in this study (33.3%) were young (21-25 years) recently employed graduates, with less than two years of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the RWF had to strictly follow the SOP to reduce the possibility of being infected by the deadly virus. However, the RWF has a high probability of being infected by the Covid-19 virus, which has a high mortality rate and causes psychological and mental trauma to both public and medical personnel [4] [5].…”
Section: Introductionmentioning
confidence: 99%